Manajemen Kinerja Aparat Pengawas Intern Pemerintahan Dalam Penerapan Inovasi Pelayanan Publik The New Public Services Pada Pemerintah Kota Jayapura - Bangun, Nehseh (JURNAL EKOLOGI BIROKRASI, 2022)
The purpose of this study is to describe the correlation between internal apparatus performance management and public service innovation based on the New Public Service paradigm. The research method used is descriptive qualitative with a case study approach. The results of the study prove validly and reliably that, the Performance Management of the Government Internal Supervisory Apparatus (APIP) Jayapura City in the application of public service innovations with the New Public Service paradigm, has not been implemented at all. Conditions that cause an increase in symptoms and poverty for the lower class. The main obstacle faced in the Performance Management of the Government Internal Supervisory Apparatus (APIP) of Jayapura City is the non-optimal preparation and determination of a permanent Performance Plan. All efforts have been made by the APIP Performance Management in Jayapura City to overcome the obstacles faced, both internally by the APIP organization and externally at other Regional Apparatus Organizations, and Village Government organizations as well as the preparation and determination of the Regional Revenue and Expenditure Budget (APBD), both through coordination coordination Regional supervision directly or through online consultation, however, has not been optimal. This condition causes impartiality to the public interest and public services which has negative implications for the 2017 Jayapura City Performance Accountability Report (LAKIP) in the applicable Government Performance Accountability System (SAKIP).